Effects of anthocyanin-rich Napier grass silage on feed intake, milk production, plasma profile, and nutritional digestibility in lactating crossbred Saanen goats - Anan Chaokaur; Janjira Sittiya; Pornpan Saenphoom; Pattaraporn Poommarin; Wilasinee Inyawilert; Jai-Wei Lee; Attapol Tiantong (Veterinary World)
Background and Aim: Anthocyanins are potent antioxidants and scavengers of free radicals found in fruits, purple corn, and other naturally occurring purple plants. Several studies have demonstrated that anthocyanins possess strong antioxidant properties and can enhance ruminant production by modulating intracellular oxidative stress and modifying ruminal fermentation. This study aimed to examine the effects of anthocyanin-rich Napier grass silage (ANS) on feed intake, nutrient digestibility, milk production, plasma profile, and antioxidant capacity in lactating crossbred Saanen goats.